Uric acid for diagnosis and risk stratification in suspected myocardial infarction. (21st December 2012) - Wildi, Karin; Haaf, Philip; Reichlin, Tobias; Acemoglu, Resat; Schneider, Jeannine; Balmelli, Cathrin; Drexler, Beatrice; Twerenbold, Raphael; Mosimann, Tamina; Reiter, Miriam; Mueller, Mira; Ernst, Susanne; et al.
Abstract Background Hypoxia precedes cardiomyocyte necrosis in acute myocardial infarction (AMI). We therefore hypothesized that uric acid – as a marker of oxidative stress and hypoxia – might be useful in the early diagnosis and risk stratification of patients with suspected AMI. Materials and methods In this prospective observational study, uric acid was measured at presentation in 892 consecutive patients presenting to the emergency department with suspected AMI. The final diagnosis was adjudicated by two independent cardiologists. Patients were followed 24 months regarding mortality. Primary outcome was the diagnosis of AMI, secondary outcome was short‐ and long‐term mortality. Results Uric acid at presentation was higher in patients with AMI than in patients without (372 μM vs. 336 μM; P < 0·001). The diagnostic accuracy of uric acid for AMI as quantified by the area under the receiver operating characteristic curve (AUC) was 0·60 (95%Cl 0·56–0·65). When added to cardiac troponin T (cTnT), uric acid significantly increased the AUC of cTnT from 0·89 (95%Cl 0·85–0·93) to 0·92 (95%Cl 0·89–0·95, P = 0·020 for comparison). Cumulative 24‐month mortality rates were 2·2% in the first, 5·4% in the second and the third and 15·6% in the fourth quartile of uric acid (P < 0·001 for log‐rank). Uric acid predicted 24‐month mortality independently. Adding uric acid to TIMI and GRACE risk score improved their prognostic accuracy as shown by an integrated discrimination improvement of 0·04 (P = 0·007) respective 0·02 (P = 0·021). Conclusions Uric acid, an inexpensive widely available biomarker, improves both the early diagnosis and risk stratification of patients with suspected AMI.